STRATEGI GURU DALAM MENANGANI KESULITAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA (STUDI KASUS DI MI MUHAMMADIYAH NUNU) - Rahmi Rahmi; Naima Naima; Anisa Anisa; Fitrirahayu Fitrirahayu; A. Ardiansyah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Early reading ability at the elementary school level plays a crucial role in helping students understand learning materials comprehensively. In practice, however, some students still experience difficulties in reading, which affects their participation in classroom learning activities. This situation was found among second-grade students at MI Muhammadiyah Nunu who encountered various obstacles in Indonesian language learning. The study explored the forms of reading difficulties experienced by students while also examining the strategies implemented by teachers and the challenges faced during the learning process. This research employed a qualitative approach using a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation related to reading instruction activities. The findings revealed that several students still had difficulty recognizing letters, combining syllables, reading fluently, and understanding simple texts. To address these difficulties, the teacher applied several strategies, including the use of visual learning media, individual guidance, gradual and repetitive reading exercises, and continuous learning motivation. Nevertheless, the implementation of these efforts was not entirely free from obstacles. Differences in students’ reading abilities, low interest in reading, limited learning assistance at home, and lack of self-confidence remained significant challenges during the learning process. The study indicates that the development of beginning reading skills requires sustained collaboration between teachers and parents to support students’ literacy growth effectively. ABSTRAK Kemampuan membaca pada tahap awal sekolah dasar memegang peranan penting dalam membantu peserta didik memahami materi pembelajaran secara menyeluruh. Kenyataannya, masih ditemukan peserta didik yang belum mampu membaca dengan baik sehingga proses belajar di kelas menjadi kurang optimal. Situasi tersebut terlihat pada peserta didik kelas II di MI Muhammadiyah Nunu yang masih menghadapi berbagai hambatan dalam pembelajaran Bahasa Indonesia. Penelitian ini menyoroti bentuk kesulitan membaca yang dialami peserta didik sekaligus menggambarkan upaya guru dalam menanganinya beserta kendala yang muncul selama proses pembelajaran berlangsung. Kajian dilakukan melalui pendekatan kualitatif dengan rancangan studi kasus. Data dikumpulkan melalui observasi kelas, wawancara dengan guru dan peserta didik, serta dokumentasi yang berkaitan dengan kegiatan pembelajaran membaca. Temuan penelitian menunjukkan bahwa sebagian peserta didik masih kesulitan mengenali huruf, merangkai suku kata, membaca dengan lancar, dan memahami bacaan sederhana. Untuk membantu peserta didik, guru menerapkan berbagai langkah seperti penggunaan media visual, pendampingan individual, latihan membaca secara bertahap dan rutin, serta pemberian motivasi belajar. Proses tersebut belum sepenuhnya berjalan tanpa hambatan karena terdapat perbedaan kemampuan membaca antarpeserta didik, rendahnya minat membaca, minimnya pendampingan belajar di rumah, dan kurangnya rasa percaya diri. Hasil penelitian memperlihatkan bahwa peningkatan kemampuan membaca permulaan membutuhkan keterlibatan guru dan orang tua secara berkelanjutan.